How is the impact of Assessment for Learning (AfL) on mathematics learning in elementary schools? - Eri Yusron; Sudiyatno Sudiyatno (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
This study aims to describe the effectiveness of the Assessment for Learning (AfL) in improving the quality of learning and mathematics learning outcomes in elementary schools. This study used a quasi-experimental method with a non-equivalent control group design. The instrument used was a test instrument with good validity, reliability, difficulty level, and different power. The non-test instrument was valid and good. Data analysis was performed using descriptive statistics, mean difference test, and variance difference test on AfL learning outcomes. The results showed that the effectiveness of learning in implementing AfL could be influenced by assessment preparation, student involvement, and follow-up assessment. The quantitative analysis results show that AfL can improve student learning outcomes; there is no mean-variance in AfL learning outcomes; There are differences in learning outcomes, and there are no variants in learning with AfL and conventional assessments. Suggestions, it is necessary to plan the assessment process, diagnose student needs and abilities. Moreover, there is a need for follow-up and feedback to see achievements.